The Future of Women in Psychological Science. (May 2021) - Gruber, June; Mendle, Jane; Lindquist, Kristen A.; Schmader, Toni; Clark, Lee Anna; Bliss-Moreau, Eliza; Akinola, Modupe; Atlas, Lauren; Barch, Deanna M.; Barrett, Lisa Feldman; Borelli, Jessica L.; Brannon, Tiffany N.; et al.
There has been extensive discussion about gender gaps in representation and career advancement in the sciences. However, psychological science itself has yet to be the focus of discussion or systematic review, despite our field's investment in questions of equity, status, well-being, gender bias, and gender disparities. In the present article, we consider 10 topics relevant for women's career advancement in psychological science. We focus on issues that have been the subject of empirical study, discuss relevant evidence within and outside of psychological science, and draw on established psychological theory and social-science research to begin to chart a path forward. We hope that better understanding of these issues within the field will shed light on areas of existing gender gaps in the discipline and areas where positive change has happened, and spark conversation within our field about how to create lasting change to mitigate remaining gender differences in psychological science.